Guyana Rice Supply Chain Risk Assessment - World Bank (World Bank, Washington, DC, 2017)
This report is the outcome of assessment and is intended as an advisory note to the Ministry of Agriculture (MoA) and Guyana Rice Development Board (GRDB) to enable them to identify a strategy and potential public investments to improve current risk-management practices in the rice supply chain. This report identifies the major risks facing the rice supply chain, ranks them in terms of their potential impact and frequency, and offers a framework for improving current risk-management practices. The recommendations and findings will provide a basis for follow-up planning work by the Government of Guyana (GoG), the World Bank, and other development partners. The findings and analysis of this initial assessment are based on a methodology designed by the Agricultural Risk Management Team (ARMT) for assessing risks in agricultural supply chains. This report provides an indicative list of potential solutions to address the dominant risks in the rice supply chain; however, the assessment or evaluation of the individual solutions was beyond the scope of this exercise. To ensure the greatest return on future public investments in implementing risk management solutions, GRDB and MoA need to undertake an exhaustive cost-benefit assessment of different options. This will enable MoA to identify and implement the necessary activities to reduce the vulnerability of the rice supply chain in Guyana.